Der "bayerische Weg" in der Datenschutzaufsicht Das "Trennungsmodell" als Grundlage für eine Zentralisierung der Datenschutzaufsicht im nicht-öffentlichen Bereich - Blum, Lucas Ben (Recht der Informationsgesellschaft, 2022)
In the early days of data protection supervision, supervision of processing in the public and non-public sectors was predominantly carried out by different authorities in the states. Today, this division of supervision (the so called "Trennungsmodell") is only found in Bavaria. Both the reasons that led to the merging of data protection authorities and the question of whether the Trennungsmodell is preferable to the so-called Einheitsmodell are examined. Relating thereto it is examined whether data protection supervision in the non-public sector needs to be reformed. With a view to a possible centralization of supervision in the non-public sector, the Trennungsmodell could ultimately prevail.